Respostas

2014-04-30T08:45:12-03:00
Acredito que seja isso.

2x  - 4 = -x +5
2x + x = 5 + 4
     3x  = 9
        x = 9/ 3
        x = 3



2014-04-30T08:45:45-03:00
2x-4= -x+5                                                                                                                    2x+x=  +5+4                                                                                                                   3x=  9                                                                                                                          x=9/3                                                                                                                            x=3